Non-invasive Prenatal Testing, What Patients Do Not Learn, May Be Due to Lack of Specialist Genetic Training by Gynecologists and Obstetricians? - Liehr, Thomas (Frontiers in Genetics, 2021)
Platforms for “non-invasive prenatal testing” (NIPT), or also referred to as “non-invasive prenatal screening” (NIPS) have been available for over 10 years, and are the most recent tools available to obtain information about genetic condition(s) of an unborn child. The highly praised advantage of NIPT-screening is that results can provide early hints on the detection of fetal trisomies and gonosomal numerical aberrations as early as the 10th week of gestation onward, without any need for invasive procedures, such as amniocenteses or alternatives. Understandably, the public along with gynecologists and obstetricians eagerly await these early test results. Their general hope for normal (=negative) test results is also justified, as in >95% of the tested cases such an outcome is to be expected. However, pregnant women can be disappointed and confused, particularly regarding the genetic information and proposed care when the results are positive, and these emotions are also common with false-positive and false-negative NIPT results. Finally, such concerns in understanding the advantages and limitations of this routinely ordered screening tool end up at Clinical Geneticists and Genetic counselors. In this review, general background on NIPT, differences of NIPT platforms, advantages and limitations of NIPT, as well as consequences of insufficient counseling before and after NIPT are summarized. To provide comprehensive care in all pregnancies situations, professionals need a careful attitude toward offering NIPT along with specially training and qualifications in counseling for these procedures. Often it is gynecologists and obstetricians who discuss the use of NIPT with patients; however, although these physicians have a highly qualified background and knowledge in their respective specialty area(s), they may lack specific training on the interpretation of NIPT-screening results. These potential knowledge gaps must be closed quickly and comprehensively by the corresponding scientific societies to ensure optimal patient care.